Catalyst‐Free Growth of Atomically Thin Bi2O2Se Nanoribbons for High‐Performance Electronics and Optoelectronics. (28th April 2021) - Khan, Usman; Tang, Lei; Ding, Baofu; Yuting, Luo; Feng, Simin; Chen, Wenjun; Khan, Muhammad Jahangir; Liu, Bilu; Cheng, Hui‐Ming
Abstract: 1D materials have attracted significant research interest due to their unique quantum confinement effects and edge‐related properties. Atomically thin 1D nanoribbons are particularly interesting because it is a valuable platform with the physical limits of both thickness and width. Here, a catalyst‐free growth method is developed and the growth of Bi2 O2 Se nanostructures with tunable dimensionality is achieved. Significantly, Bi2 O2 Se nanoribbons with a thickness down to 0.65 nm, corresponding to a monolayer, are successfully grown for the first time. Electrical and optoelectronic measurements show that Bi2 O2 Se nanoribbons possess decent performance in terms of mobility, on/off ratio, and photoresponsivity, suggesting their promise for devices. This work not only reports a new method for the growth of atomically thin nanoribbons but also provides a platform to study properties and applications of such nanoribbon materials at a thickness limit. Abstract : Atomically thin nanoribbons represent a valuable platform to exploit the property of materials with physical limits of both thickness and width. A catalyst‐free chemical vapor deposition approach is developed to grow Bi2 O2 Se nanoribbons down to the monolayer. Electrical and optoelectronic measurements show that Bi2 O2 Se nanoribbons possess decent performance in terms of mobility, on/off ratio, and photoresponsivity, suggesting their promise for devices.